Sample Size Calculation of Clinical Trials Published in Two Leading Endodontic Journals - Shahravan, Arash; Haghdoost, Ali-Akbar; Rad, Maryam; Hashemipoor, Maryamalsadat; Sharifi, Maryam (Iranian Endodontic Journal, 2013)
Introduction: The purpose of this article was to evaluate the quality of sample size calculation reports in published clinical trials in Journal of Endodontics and International Endodontic Journal in years 2000-1 and 2009-10. Materials and Methods: Articles fulfilling the inclusion criteria were collected. The criteria were: publication year, research design, types of control group, reporting sample size calculation, the number of participants in each group, study outcome, amount of type I (α) and II (β) errors, method used for estimating prevalence or standard deviation, percentage of meeting the expected sample size and considering clinically importance level in sample size calculation. Data were extracted from all included articles. Descriptive analyses were conducted. Inferential statistical analyses were done using independent T-test and Chi-square test with the significance level set at 0.05. Results: There was a statistically significant increase in years between 2009 and 10 compared to 2000-1 in terms of reporting sample size calculation (P=0.002), reporting clinically importance level (P=0.003) and in samples size of clinical trials (P=0.01). But there was not any significant difference between two journals in terms of reporting sample size calculation, type of control group, frequency of various study designs and frequency of positive and negative clinical trials in different time periods (P>0.05). Conclusion: Sample size calculation in endodontic clinical trials improved significantly in 2009-10 when compared to 2000-1; however further improvements would be desirable.